• Join over 1.2 million students every month
• Accelerate your learning by 29%
• Unlimited access from just £6.99 per month
Page
1. 1
1
2. 2
2
3. 3
3

# Maths Grid Coursework

Extracts from this document...

Introduction

I will now investigate different size grids. An 11 by 11 1 2 3 n=24 12 13 14 23 24 25 T=n+ (n-11) + (n-23) + (n-22) + (n-21) T=5n-77 Now test this: 24 25 26 n=47 35 36 37 T=5n - 77 46 47 48 T= (5 x 47) - 77 T=158 Check 24+25+26+36+47 =158 So this formula does work. A 6x6 grid 1 2 3 n=14 7 8 9 13 14 15 T=0 + (n-6) + (n-12) + (n-13) + (n -11) T=5n-42 Now to test it. ...read more.

Middle

(With the same amount of numbers in side the T shape) The numbers which are underlined are all divisible by 7. This means that if you know the grid size you can multiply it by 7 and it would give you the number that you would subtract from the Tnumber. From this we can make a general formula for any size grid and any Tnumber. g=grid size The General Formula is: T=5n-7g N.B This formula only applies to a T this way up: Formulae Formula Shape of 'T' 1)T=5n-3 T(in 9 by 9 grid) ...read more.

Conclusion

Therefore I think that the formula is: T=5n+7g on any grid size. Test on 9 By 9 1 2 3 T= (5x2) + (7x9) 10 11 12 T= 10+63 19 20 21 T= 73 Check 2+11+20+19+21=73 This means that this formula is correct; I will do 1 more test just to make sure. Test on 5 by 5 7 8 9 T= (5x8) + (7x5) 12 13 14 T= 40+35 17 18 19 T=75 Check 8+13+17+18+19=75 I now believe that the formula is: T=5n+7g works for an upside down T anywhere on a grid of any size. I will now investigate a T like this: ...read more.

The above preview is unformatted text

This student written piece of work is one of many that can be found in our GCSE T-Total section.

## Found what you're looking for?

• Start learning 29% faster today
• 150,000+ documents available
• Just £6.99 a month

Not the one? Search for your essay title...
• Join over 1.2 million students every month
• Accelerate your learning by 29%
• Unlimited access from just £6.99 per month

# Related GCSE T-Total essays

1. ## T-Total Maths

T=5N+63 I tested that when: T-number=62 T-total=373 N = 2 3 4 5 T = 73 78 83 88 T-number T = (5x2) +63 = 10+63 T = 73 T-total This equation has produced its first correct answer. I will carry on and test T-shape I know the T-total for N = 3 T = (5 x 3)

2. ## T-Total Maths coursework

To prove the formula: T= N+N-9+N-17+N-16+N-15 T= 5N-56 How the formula works there are some example shown in below are: Formula: T=5N-56 N= 18 19 20 21 T= 34 39 44 49 T-number T= (5x18)-56 = 80-56 T= 34 T-total This equation has produced its first correct answer.

1. ## T-Shapes Coursework

Every square in the "T" is referred to in terms of n and so with 4 squares added together, there are 4n. The "g" comes from the "Sum of the Tail", which is g more than the Middle Number. The "Sum of the Wing" is 3n because there are 3 "n"s present in the 3 squares of the wing.

2. ## T-Shapes Coursework

Testing Our Formula Okay, so we have found a reasonable formula, so let's test it, using the first T-shape in the 9x9 grid as an example: 1 2 3 11 20 Our formula: Tt = 5n - 63 In this case, n = 20, and the Tt = T-Total.

1. ## T totals. In this investigation I aim to find out relationships between grid sizes ...

+ 2 t=5(44-27) +2 t=5(17) + 2 t=87 Thus proving my theory correct on this grid size, to double check this I will use a different grid size, and a different translation / rotation combination, in this case 180 degrees clockwise so the formula will read t=5((v+b)-ag)

2. ## Maths Coursework T-Totals

40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 T=(5x14)

1. ## T-Total Coursework

187 The following shows a T-Shape with the used formula to explain what the formula for each number is when we have the T-Number. N - 2G - 1 N - 2G N - 2G +1 N - G N PART 2 This next section involves using grids of different sizes and then translating the T-Shape to different positions.

2. ## Maths coursework

minus 17 To find T, I must add up what is in the t-shape and simplify the out come: T = N + N- 9 + N- 19 + N- 18 + N- 17 T = 5N - 63 Therefore the overall equation is T = 5N - 63 To

• Over 160,000 pieces
of student written work
• Annotated by
experienced teachers
• Ideas and feedback to